Trophoblast glycoprotein is required for efficient synaptic vesicle exocytosis from retinal rod bipolar cells - Wakeham, Colin M.; Shi, Qing; Ren, Gaoying; Haley, Tammie L.; Duvoisin, Robert M.; von Gersdorff, Henrique; Morgans, Catherine W. (Frontiers in Cellular Neuroscience, 2023)
Rod bipolar cells (RBCs) faithfully transmit light-driven signals from rod photoreceptors in the outer retina to third order neurons in the inner retina. Recently, significant work has focused on the role of leucine-rich repeat (LRR) proteins in synaptic development and signal transduction at RBC synapses. We previously identified trophoblast glycoprotein (TPBG) as a novel transmembrane LRR protein localized to the dendrites and axon terminals of RBCs. We now examine the effects on RBC physiology and retinal processing of TPBG genetic knockout in mice using immunofluorescence and electrophysiological techniques. The scotopic electroretinogram showed a modest increase in the b-wave and a marked attenuation in oscillatory potentials in the TPBG knockout. No effect of TPBG knockout was observed on the RBC dendritic morphology, TRPM1 currents, or RBC excitability. Because scotopic oscillatory potentials primarily reflect RBC-driven rhythmic activity of the inner retina, we investigated the contribution of TPBG to downstream transmission from RBCs to third-order neurons. Using electron microscopy, we found shorter synaptic ribbons in TPBG knockout axon terminals in RBCs. Time-resolved capacitance measurements indicated that TPBG knockout reduces synaptic vesicle exocytosis and subsequent GABAergic reciprocal feedback without altering voltage-gated Ca 2+ currents. Thus, TPBG is required for normal synaptic ribbon development and efficient neurotransmitter release from RBCs to downstream cells. Our results highlight a novel synaptic role for TPBG at RBC ribbon synapses and support further examination into the mechanisms by which TPBG regulates RBC physiology and circuit function.Retinal rod bipolar cells (RBCs) must reliably detect and transform visual signals over a wide range of luminance and contrast conditions. To achieve this, the presynaptic active zones RBCs contain specialized synaptic ribbons that cluster synaptic vesicles near the presynaptic membrane and promote extremely precise, rapid, and sustained neurotransmitter release in response to graded changes in membrane potential. Here we show that knockout of the leucinerich repeat protein trophoblast glycoprotein (TPBG) reduces synaptic ribbon length and attenuates synaptic vesicle exocytosis from RBC axon terminals. Therefore, we propose that TPBG is required for synaptic ribbon development and efficient synaptic vesicle exocytosis at RBC synapses.